Quality of Sustainability Disclosure, Foreign Board, and Firm Performance? Evidence from Indonesia - ARMADANI, ARMADANI; ZAREFAR, ARUMEGA (Department of Accounting, Faculty of Economics, Universitas Negeri Semarang, 2023)
Purpose: This study intends to investigate the impact of sustainability disclosure and foreign board quality on firm performance. This research also analyzes the impact of each category of sustainability disclosure quality on company performance.Method: General Least Square (GLS) is the analytic method used to test the hypothesis. 315 observations from 46 chemical and basic industries compose the sample.Findings: This study reveals that the quality of sustainability disclosure and the presence of foreign boards have a considerable favorable impact on the performance of companies. Then, the additional study revealed that the social and environmental categories had a considerable positive impact on the organization’s success. In addition, there is no correlation between the economic category and the company’s performance. Novelty: To the author’s knowledge, this is the first study to examine Indonesia’s chemical and basic industrial sectors. This research is distinctive in that it employs a more thorough sustainability disclosure quality measurement, namely developing a measuring instrument with analysis content based on GRI Guidance. Then, this study examines the relationship between the quality of sustainability disclosure and firm performance.